2021
DOI: 10.18865/ed.31.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Traversing Traditions: Prenatal Care and Birthing Practice Preferences Among Black Women in North Florida

Abstract: Objectives: Our goal was to explore prenatal practices and birthing experiences among Black women living in an urban North Florida community.Design: Non-random qualitative study.Setting: Private spaces at a convenient loca­tion selected by the participant.Participants: Eleven Black women, aged 25-36 years, who were either pregnant or had given birth at least once in the past five years in North Florida.Methods: Semi-structured interviews were completed in July 2017, followed by the­matic analysis of interview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Thirteen (54.5%) of the 22 studies included self‐reported data on participant racial and ethnic identity. Two studies reported binary race/ethnicity categories among 194 participants: White or “Ethnic/Minority.” 40,42 The remaining 11 studies reported more specific race/ethnicity details among 952 participants 38,43–47,49–52,56 . Among these participants, 539 (56.6%) participants identified as White or Caucasian, 287 (30.1%) identified as Black or African American, 54 (5.7%) identified as Asian, 16 (1.7%) as Hispanic or Latinx, 9 (1.0%) as American Indian or Alaskan Native, 4 (0.4%) as Native Hawaiian or Pacific Islander, and 2 (0.2%) as Middle‐Eastern.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirteen (54.5%) of the 22 studies included self‐reported data on participant racial and ethnic identity. Two studies reported binary race/ethnicity categories among 194 participants: White or “Ethnic/Minority.” 40,42 The remaining 11 studies reported more specific race/ethnicity details among 952 participants 38,43–47,49–52,56 . Among these participants, 539 (56.6%) participants identified as White or Caucasian, 287 (30.1%) identified as Black or African American, 54 (5.7%) identified as Asian, 16 (1.7%) as Hispanic or Latinx, 9 (1.0%) as American Indian or Alaskan Native, 4 (0.4%) as Native Hawaiian or Pacific Islander, and 2 (0.2%) as Middle‐Eastern.…”
Section: Resultsmentioning
confidence: 99%
“…One study mentioned all three options; however, the author’s reference to birth centers referred specifically to in‐hospital birth centers 41 . A total of eight studies dichotomized choices between home and hospital births 41–48 . Seven studies focused solely on home birth 37,49–54 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations